The occurrence of asthma in an extensive-stage small-cell lung cancer patient after combination therapy with atezolizumab and anlotinib: a case report - Deng, Wang; Chen, Juan; Deng, Xin-Yu (Frontiers in Immunology, 2024)
Background: Extensive-stage small-cell lung cancer (ES-SCLC) is highly malignant with early metastasis and easy recurrence.Since therapeutic options are limited, ES-SCLC has a characteristically short survival period and a very poor prognosis.A combination of immune checkpoint inhibitors (ICIs) and anti-angiogenic drugs can achieve promising efficacy and safety in ES-SCLC patients as a second-line or subsequent treatment, extending survival to some extent.However,clinical outcomes remain mostly unsatisfactory, and are sometimes marred by treatment-related adverse events.Case presentation:A 57-year-old woman with ES-SCLC was administered a combination therapy of atezolizumab (a PD-L1 inhibitor) and anlotinib (an orally multi-targeted tyrosine kinase inhibitor [TKI]). She has survived for 22 months with no disease progression during 28 courses of therapy.Unexpectedly, and despite having no history of asthma,the patient developed asthma while receiving the above regimen.It is possiblely related to T cell activation and tumor immune microenvironment,which induce allergic inflammation after PD-L1 blockade.We are the first to report an asthma-negative patient with ES-SCLC that developed asthma after receiving atezolizumab plus anlotinib.Although this combination therapy may effectively extend survival in SCLC, asthmatic symptoms should be closely monitored.